Short-Term Water- and Land-Based Exercise Training Comparably Improve Exercise Capacity and Vascular Function in Patients After a Recent Coronary Event: A Pilot Randomized Controlled Trial - Vasić, Danijela; Novaković, Marko; Božič Mijovski, Mojca; Barbič Žagar, Breda; Jug, Borut (Frontiers in Physiology, 2019)
Background. We hypothesized that a two-week twice daily aquatic endurance plus calisthenics exercise training program: increases aerobic exercise capacity (peak oxygen uptake/V̇O2peak),improves endothelium-dependent flow-mediated vasodilation (FMD) and reduces circulating markers of low-grade inflammation and hemostasis, as compared to land-based endurance plus calisthenics exercise training or no exercise in patients undergoing short-term residential cardiac rehabilitation after a recent coronary artery disease (CAD) event. Methods. Patients with a recent myocardial infarction or revascularization procedure were randomized into two interventional groups and a control group. The interventional groups underwent supervised aerobic endurance plus calisthenics exercise training either in thermo-neutral water or on land at moderate-intensity for 30 minutes twice daily for two weeks. At baseline and after the intervention period, all participants underwent estimation of aerobic exercise capacity, brachial artery flow-mediated dilatation, markers of cardiac dysfunction (NT-proBNP,), inflammation (hsCRP, IL-6, IL-8, IL-10), cell adhesion (ICAM, P-selectin), hemostasis (fibrinogen, D-dimer). Results. A total of 89 patients (mean age 59.9±8.2 years, 77.5% males, V̇O2peak at baseline 14.8±3.5 ml/kg/min) completed the study. Both exercise modalities were safe (no significant adverse events recorded) and associated with a significant improvement in V̇O2peak as compared to controls: age and baseline V̇O2peak-adjusted end-of study V̇O2peak increased to 16.7 (95% CI 16.0–17.4) ml/kg/min with land-based training (p<0.001 for change from baseline) and to 18.6 (95% CI 17.9–19.3) ml/kg/min with water-based training (p<0.001 for change from baseline), but not in controls (14.9 ml/kg/min; 95% CI 14.2–15.6; p=0.775 for change from baseline). FMD also increased in both intervention groups (from 5.5 to 8.8%, p<0.001 with land-based, and from 7.2 to 9.2%, p<0.001 with water-based training, respectively), as compared to controls (p for change 0.629). No significant changes were detected in biomarkers of inflammation, cell adhesion or hemostasis, whereas levels of NT-proBNP ( marker of cardiac dysfunction) decreased in the water-based training group (p=0.07 vs. controls). Conclusion. Endurance plus callisthenics exercise training in thermo-neutral water is safe, and improves aerobic exercise capacity and vascular function in patients undergoing short-term residential cardiac rehabilitation after a recent CAD event. This study is registered with ClinicalTrials.gov number NCT02831829